PROCESS COSTİNG IN THE PRODUCTİON ENTERPRİSES: AN APPLİCATİON ON THE BEEKEEPİNG SECTOR IN MUĞLA (Third Sector Social Economic Review, 2021)
The purpose of the study is to reveal the production and cost structure of the basic honeycomb sector and to calculate the unit cost with the most ideal cost method for the sample business. Within this scope, by revealing the structure of the sector that produces beekeeping products, beeswax and basic honeycomb products, which is a developing sector, it is explained how the stage cost system, which is necessary for determining the costs correctly and making the right decisions, will be applied in a production company operating in Muğla.
Keywords: Cost Accounting; Cost Methods; Phase Cost Method; Beekeeping; Basic Honeycomb